so basically we only use the associative property of multiplication and one of the laws of exponents
associative=a(bc)=(ab)c also law of exponent=a^x times a^y=a^(x+y)
(3.6 times 10^2) times (2.8 times 10^2) associative 3.6 times 10^3 times 2.8 times 10^2 3.6 times 2.8 times 10^2 times 10^2 law of exponents 10^2 times 10^2=10^(2+2)=10^4 3.6 times 2.8=10.08 the answer is 10.08 times 10^4 or (10.08*10^4) or (1.001*10^5)
the second one
(3.6 times 10^6) times (2.2 times 10^-4) associative 3.6 times 10^6 times 2.2 times 10^-4 3.6 times 2.2 times 10^6 times 10^-4 law of exponents 10^6 times 10^-4=10^(6-4)=10^2 3.6 times 2.2=7.92 the answer is 7.92 times 10^2 or (7.92*10^2)